A rare case of spontaneous spinal epidural hematoma with spontaneous resolution (Indian Journal of Case Reports, 2024)
Spontaneous spinal epidural hematoma (SSEH) is an uncommon cause of acute spinal cord compression. It is a neurological emergency that requires urgent imaging and appropriate treatment to prevent permanent neurological sequelae. Here, we present the case of a 30-year-old male with no known comorbidities who presented to the emergency department with a history of sudden onset of upper backache and chest discomfort followed by bilateral lower limb weakness. On examination, the blood pressure was 220/120 mmHg, and neurological examination showed decreased tone and power of 2/5 in bilateral lower limbs. In view of the initial chest discomfort, a cardiac evaluation was done, which was normal, followed by magnetic resonance imaging of the whole spine, which showed a lesion in the anterior epidural space suggestive of hematoma, causing spinal cord compression. A final diagnosis was C6-T2 dorsal SSEH secondary to a hypertensive emergency.